Effect of antihistamine-releasing contact lenses on ocular symptoms and treatment behavior in patients with seasonal allergic conjunctivitis: A retrospective study - Kenta Fujio; Jaemyoung Sung; Kunihiko Hirosawa; Masahiro Yamaguchi; Hiroshi Toshida; Keiji Inagaki; Gaku Ishida; Motozumi Itoi; Kazushige Sado; Hiroo Hayatsu; Hirayama Nobutaka; Junji Ono; et al. (Heliyon, 2024)
Purpose: This study aimed to compare subjective allergic conjunctivitis symptoms and anti-allergic eye drop use patterns between antihistamine-releasing contact lens users and daily disposable soft contact lens users during Japan's hay fever season. Methods: This web-based retrospective cohort study included daily disposable soft contact lens or antihistamine-releasing contact lens users with a history of seasonal allergic conjunctivitis who regularly used daily disposable soft contact lenses since the previous year. The total ocular symptom score (range 0–20) based on 5-item questionnaire scores and time from the start of the hay fever season to the initiation of anti-allergic eye drop treatment were compared between antihistamine-releasing contact lens users and daily disposable soft contact lens users. Results: The study included 24 participants: 17 using daily disposable soft contact lenses and 7 using antihistamine-releasing contact lenses. Antihistamine-releasing contact lens users experienced a greater reduction in total ocular symptom score from 2021 to 2022 compared with daily disposable soft contact lens users (mean total ocular symptom score [standard deviation]: daily disposable soft contact lens: −0.65 [1.4], antihistamine-releasing contact lens: −4.7 [3.6]; n = 24; Mann–Whitney U test, P = 0.010). Fourteen daily disposable soft contact lens users and five antihistamine-releasing contact lens users eventually required anti-allergic eye drops. Kaplan–Meier analysis revealed a significant delay in the initiation of anti-allergic eye drop treatment among those using antihistamine-releasing contact lenses compared with those using daily disposable soft contact lenses (median days, daily disposable soft contact lenses: 19 days, antihistamine-releasing contact lens: 57 days; n = 24; log-rank test, P = 0.045). Conclusions: Antihistamine-releasing contact lenses can potentially mitigate worsening ocular allergic responses during the hay fever season when used appropriately as a preventive measure.